PENGEMBANGAN E-MODUL BERBASIS APLIKASI FLIPBOOK KELAS IV SUBTEMA INDAHNYA KEBERAGAMAN BUDAYA - Annisa Daniatus Salma; Tustiyana Windiyani; Ratih Purnamasari (STKIP Subang, 2023)
This study aims to determine the feasibility of an electronic module developed based on a flipbook application as teaching material for elementary school students. This research was conducted using the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). This study aims to produce an e-module product based on a flipbook application, theme 7 sub-theme 2 learning 2 The Beauty of Cultural Diversity in class IV Sekolah Dasar Regency with a total of 30 students as respondents. To determine the feasibility test, validation sheets were used by e-module experts and material experts with the results obtained in the appropriate category. The results of the validation of the media, language, and material aspects show that the flipbook e-module is very feasible to use with an average percentage gain of 90.45%. While the results of the study on student responses showed that the flipbook e-module was feasible to use with an acquisition of 82,31%. Based on the results of the study showed that the e-module based on the flipbook application can be categorized as feasible, effective, and practical for students to use in learning.